Implementasi Kebijakan Penanggulangan Kemiskinan di Kota Medan Dalam Perspektif Ekonomi Politik - Muhammad Ardian; Arief Marizki Purba (PERSPEKTIF, 2021)
This research aims to describe and analyze the implementation of the Poverty Reduction Policy in the Perspective of Political Economy in Medan Belawan District, Medan City. The research method used is descriptive research method with a qualitative approach. The results showed that the implementation of poverty reduction policies in Medan Belawan sub-district from the perspective of political economy has been running quite well. The whole series or process of activities starting from the initial socialization, reflecting on poverty, implementing the program, monitoring the program all went quite well. The success of the Poverty Reduction Policy is greatly supported by the effectiveness of the implementing organizations in providing learning, mentoring, independence, for the poor. The obstacle that occurs in the implementation of this policy is that there are still poor people, most of whom are traditional fishing workers who have not received the benefits of assistance programs from the Government. This caused some of their children to drop out of school to work to help their parents.